Towards an inclusive language curriculum: re-orienting textbooks images and messages in respect of gender - Letsela, Lati Martha (Centre for Applied Language and Literacy Studies and Services in Africa, 2016)
Having ratified and signed many international conventions and declarations on mainstreaming gender issues, Lesotho was compelled to review some of its policies and laws to ensure equitable distribution of resources to both female and male citizens in the name of democracy and development. This study sought to establish whether progress has been made in the field of education in promoting gender sensitivity and removing gender bias and stereotypes, which among other things, manifest themselves in textbooks through textual messages and images. Taken as one of the agents of socialisation in Lesotho, it is believed that textbooks can foster either gender sensitivity or negative gender discrimination; hence this study examines primary language textbooks to ascertain their role in this regard. Seven language textbooks, two written in Sesotho and five in English, were analysed in terms of gender. Gender was understood as a social phenomenon, and this made it imperative for the study to draw on theories and perspectives from different social disciplines. In the main, however, the analysis was informed by feminist theories, notably feminist stylistics as postulated by Mills (1995c). Psychoanalytical perspectives were employed in an attempt to explain the impact of under-representation, stereotypical, and sexist language, on the identities of the affected pupils. The study has established that the examined prescribed primary school language textbooks are not gender-sensitive and it has therefore recommended guidelines for use by textbooks evaluators, selectors, editors, publishers, authors, and other stakeholders in textbook production and procurement processes. Both quantitative and qualitative analytical methods were used in order to cater for quantifiable data and discourse-type data.